Video streaming over WiMAX networks - Maki Mohd Ahmed, Sheraz Maki Mohd Ahmed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Abdullah, Tahani Abdullah; Yousif, Marwa (IJCSNS, 2014)
WiMAX IEEE802.16 is a technology standard for long range wireless networks, it depends on two concepts, the base station,which is installed by the service provider, and the receivers, that are installed at the client’s premises. This is paper focuses on studying video streaming over WiMAX. The multicast/broadcast service (MBS) is a feature provided by WiMAX technology and works under MAC layer, which provides connection oriented and quality of service support. Streaming video over an MBS is more efficient in terms of resource management by focusing on a certain area and ensuring high bit rate that results in a higher quality service